Dog owners’ intention to control rabies and their willingness to pay for rabies vaccine in Northwestern Ethiopia - Mengie, F.; Jemberu, Wudu T.; Mulugeta, Y.; Molla, W.; Mekonnen, S.A. (2025)
Rabies is a viral disease that affects both animals and humans. Effectiveness of a rabies control measures depends on collaboration of dog owners. This study was conducted in North West Ethiopia to understand the intention and willingness to pay (WTP) of dog owners related to rabies control and factors affecting rabies control measures. Data was collected from 423 randomly selected dog owners in four Gondar zones, North West Ethiopia. The theory of planned behavior was used to explore the intention of dog owners towards implementing rabies control measures. Contingent evaluation method was used to evaluate WTP for rabies vaccine. Logistic regression analysis was used to test association with factors. Large majority of dog owners had positive intention to control rabies by vaccination of dogs (97% free of charge, 93% with fair price) and 94% by leashing. Majority of dog owners had a positive attitude (AT), positive subjective norms (SN) and positive perceived behavioral control (PBC) towards controlling rabies. Dog owners’ AT and SN were positively associated with intention to vaccinate dogs. Male dog owners and dog owners belonging to lower age groups had significantly higher AT towards leashing dogs. Sixty two percent of dog owners were WTP for the suggested price bid amounts; but, in general, their number decreased when price of the vaccine increased. The mean WTP for rabies vaccine was 59.25 Ethiopian Birr (1.14 USD) per year. Monthly income was associated (P < 0.05) with WTP for rabies vaccine. Dog owners who had higher income had higher odds but those who did not vaccinate their dogs in the last two years had lower odds of WTP for rabies vaccine. Intervention directed at changing AT and SN is important to increase intention of dog owners; nevertheless subsidizing rabies vaccine increase dog owners participation in dogs vaccination campaign.